A New Empirical Model for Heavy Metals Biosorption - Munaf*, Edison; Abdullah, Zulfi; Innes Kurniawan, Meilia; Nazaruddin, Nazris; Zein, Rahmiana; Aziz, Hermansyah (Asian Journal of Chemistry, 2014)
A new model based on an empirical approach is proposed to apply to the biosorption of heavy metals. This model is implemented for four sets of experimental data to study the effect of concentration of Cr(III), Cr(VI), Cd(II) and Zn(II) on the sorption capacity by Arenga pinnata fruit shell. Six conventional models namely, Langmuir, Freundlich, Sips, Toth, Redlich-Peterson and Khan have been used for the comparison of new model on the biosorption process. Coefficient determination of four consecutive data for the effect of concentration of Cr(III), Cr(VI), Cd(II) and Zn(II) calculated using Langmuir, Freundlich, Sips, Toth, Redlich-Peterson and Khanishoterm are 0.76629, 0.72368, 0.88256, 0.80818, 0.84782 and 0.31096, respectively. On the other hand, coefficient determination of a new model using a non-linear regression with Levenberg-Marquardt algorithmis 0.91792. This means that a new proposed model shows more better results compared with other conventional reference models.